Design and Implementation of an Ultrasonic Device Prototype with Arduino - Abdulkhudhur, Kawthar Ali (American Journal of Botany and Bioengineering, 2025)
Sonography is versatile diagnostic approach used for examining patients. In physics, the term ‘ultrasound’ applies to all caustic energy (longitudinal, mechanical wave) with frequency above the audible range of human hearing. which its range 20Hz-20KHz and the ultrasound frequency its greater than 20KHz (it’s not different from normal sound wave in physical properties except human cannot hear it). this project provides an examination of the patient by using ultrasound technology based on uses a small probe called a transducer and using 5MHz transducer sensor. Ultrasound gel is placed directly on the part of the body that is to be examined and the transducer is then applied. High-frequency sound waves travel from the probe through the gel into the body. The transducer probe collects the sounds waves that bounce back to create an image which can then be viewed in real-time via a LCD TFT screen on arduino due microcontroller. By programming the microcontroller and its code attached to Annex No.1 at the end of the research.